The correlation between total quality management with teacher performance in special education - Mufidah, Aulia Maya; Yusuf, Munawir; Widyastono, Herry (Journal of Education and Learning (EduLearn), 2025)
Total quality management (TQM) in education is a management theory that directs service providers to carry out quality improvement programs on an ongoing basis that focuses on achieving customer satisfaction in improving the quality of learning. This aim study analyzed the relationship between total quality management and teacher performance in special education. This research used correlational research with a quantitative methodology. Data analysis techniques in this study were instrument tests (validity and reliability). The sample consisted of 132 respondents, including school principals and teachers. Data collection used questionnaires. The quantitative descriptive analysis technique was then applied to the data. The product-moment correlation was used in the hypothesis testing. The findings demonstrated a strong and favorable correlation between teacher effectiveness and overall quality management.